Extension of continental lithosphere in rifted margins: a review of thinning mechanisms - Tugend, Julie; Mohn, Geoffroy; Duretz, Thibault; Petri, Benoit; Le Pourhiet, Laetitia (Comptes Rendus. Géoscience, 2024)
International audience Crustal geometries imaged at rifted margins show contrasted first-order morphologies (wide and narrow, symmetric or asymmetric conjugates). This contribution aims to review the mechanisms of continental lithospheric thinning and types of extensional structures that control the formation of rifted margins. We illustrate, using a two-layer numerical model (one for the crust and one for the mantle), how different modes of lithospheric thinning shape the end-member crustal geometries of rifted margins depending on the initial thermal conditions and extension rates. As already known, the activation of narrow or wide modes of lithospheric thinning depends on the rheological behaviour of the lower crust and its efficiency as a decoupling layer. Morphologies generated by narrow lithospheric thinning modes compare well with Atlantic-type rifted margins (e.g., Iberia–Newfoundland) while wide lithospheric thinning modes better apply to marginal seas characterized by higher initial geothermal gradients (e.g., South China Sea). Finally, we also emphasize that continental lithosphere thinning is depth-dependent, part of which is transient and cannot easily be measured in natural systems. L’architecture crustale des marges passives imagée par les méthodes géophysiques est contrastée montrant des morphologies tantôt larges ou étroites, les profils conjugués pouvant être symétriques ou asymétriques. Cette contribution présente les mécanismes d’amincissement de la lithosphère continentale et les différents types de structures extensives qui contrôlent la formation des marges passives. L’utilisation d’un modèle à deux couches (une pour la croûte et une pour le manteau), permet d’illustrer comment les différents modes d’amincissement de la lithosphère façonnent l’architecture premier ordre des marges passives pour différents taux d’extension et conditions thermiques initiales. Comme précédemment démontré, l’activation d’un mode d’amincissement de la lithosphère étroit/localisé ou large/distribué dépend du ...